МАТЕМАТИЧНЕ ПРОГНОЗУВАННЯ ЗМІН МАСООБМІНУ ТА ЯКОСТІ ВОД У КЕРЧЕНСЬКІЙ ПРОТОЦІ ВНАСЛІДОК БУДІВНИЦТВА ДАМБИ В РАЙОНІ ОСТРОВА ТУЗЛА - Кресин, В. С.; Баранник, В. А. (Marine Ecological Journal, 2023)
The simulation model of the water and mass exchange in the Kerch straight is developed to predict the water quality changes under impact of dam near the Tuzla Isl. The Kerch Strait is conditionally separated on three boxes having the liquid boundaries with Black and Azov Seas. The water quality is described by the content of salinity, dissolved oils, total nitrogen and phosphorous within boxes. The unsteady hydrodynamic circulation is modeled as random consequence of advective flows providing for the water and mass transfer through the liquid boundaries of boxes. Tamansky Gulf is expected to be the most negatively impacted part of Kerch Strait. The water quality is declined through the increase of dissolved total nitrogen and phosphorous is predicted to bring about rising of eutrophication.